Revitalisasi Manajemen BUMDesa dalam Pengembangan UMKM di Desa Watesari Kec Balongbendo Sidoarjo - Siti Ngaisah (Universitas 45 Surabaya, 2022)
Watesari Village, Balongbendo District, Sidoarjo Regency, East Java Province. The boundaries of Watesari Village are in the north with Jabaran Village, in the south with Gagang Kepuhsari Village, in the east with Seketi Village and in the west with Suwaluh Village. Watesari Village is known as the Starfruit-Producing Tourism Village. Improvement of the management system to accelerate the business growth of BUMDes Bina Sejahtera Watesari as part of efforts to improve the welfare of rural communities. The initiation of the development of the Bum Desa Bina Sejahtera business in Watesari village in the form of Watesari Starfruit Agrotourism business, is a good concept and action, but support is still needed in the form of an adequate management system based on business principles and financial rules, in order to be able to achieve its goal, namely the achievement of improving the welfare of the residents of Watesari village.